Antibody response to a third SARS‐CoV‐2 vaccine dose in recipients of an allogeneic haematopoietic cell transplantation. (16th November 2022) - Bankova, Andriyana K.; Pasin, Chloé; Huang, Alice; Cicin‐Sain, Caroline; Epp, Selina; Audige, Annette; Mueller, Nicolas J.; Nilsson, Jakob; Vilinovszki, Oliver; Nair, Gayathri; Wolfensberger, Nathan; Hockl, Philipp; et al.
Summary: Allogeneic haematopoietic cell transplantation (allo‐HCT) recipients show impaired antibody (Ab) response to a standard two‐dose vaccination against severe acute respiratory syndrome coronavirus‐2 and currently a third dose is recommended as part of the primary vaccination regimen. By assessing Ab titres 1 month after a third mRNA vaccine dose in 74 allo‐HCT recipients we show sufficient neutralisation activity in 77% of the patients. Discontinuation of immunosuppression before the third vaccine led to serological responses in 50% of low responders to two vaccinations. Identifying factors that might contribute to better vaccine responses in allo‐HCT recipients is critical to optimise current vaccination strategies.